Viral load of patients with hantavirus pulmonary syndrome in Argentina - Bellomo, Carla (2015)
Fil: Bellomo, Carla. ANLIS Dr.C.G.Malbrán. Instituto Nacional de Enfermedades Infecciosas. Departamento de Virología. Servicio de Biología Molecular; Argentina.